Reverse phase HPLC method for detection and quantification of lupin seed ?-conglutin - Mane, S.; Bringans, S.; Johnson, Stuart; Pareek, Vishnu; Utikar, Ranjeet (Elsevier BV, 2017)
© 2017 Elsevier B.V. A simple, selective and accurate reverse phase HPLC method was developed for detection and quantitation of ?-conglutin from lupin seed extract. A linear gradient of water and acetonitrile containing trifluoroacetic acid (TFA) on a reverse phase column (Agilent Zorbax 300SB C-18), with a flow rate of 0.8 ml/min was able to produce a sharp and symmetric peak of ?-conglutin with a retention time at 29.16 min. The identity of ?-conglutin in the peak was confirmed by mass spectrometry (MS/MS identification) and sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) analysis. The data obtained from MS/MS analysis was matched against the specified database to obtain the exact match for the protein of interest. The proposed method was validated in terms of specificity, linearity, sensitivity, precision, recovery and accuracy. The analytical parameters revealed that the validated method was capable of selectively performing a good chromatographic separation of ?-conglutin from the lupin seed extract with no interference of the matrix. The detection and quantitation limit of ?-conglutin were found to be 2.68 µg/ml and 8.12 µg/ml respectively. The accuracy (precision and recovery) analysis of the method was conducted under repeatable conditions on different days. Intra-day and inter-day precision values less than 0.5% and recovery greater than 97% indicated high precision and accuracy of the method for analysis of ?-conglutin. The method validation findings were reproducible and can be successfully applied for routine analysis of ?-conglutin from lupin seed extract.